Toward improved prediction of risk for atopy and asthma among preschoolers: A prospective cohort study - Holt, P.; Rowe, J.; Kusel, M.; Parsons, F.; Hollams, E.; Bosco, A.; McKenna, K.; Subrata, L.; de Klerk, N.; Serralha, M.; Holt, B.; Zhang, Guicheng; et al. (2010)
Background: Atopy and asthma are commonly initiated during early life, and there is increasing interest in the development of preventive treatments for at-risk children. However, effective methods for assessing the level of risk in individual children are lacking. Objective: We sought to identify clinical and laboratory biomarkers in 2-year-olds that are predictive of the risk for persistent atopy and wheeze at age 5 years. Methods: We prospectively studied 198 atopic family history-positive children to age 5 years. Clinical and laboratory assessments related to asthma history and atopy status were undertaken annually; episodes of acute respiratory illness were assessed and classified throughout and graded by severity. Results: Aeroallergen-specific IgE titers cycled continuously within the low range in nonatopic subjects. Atopic subjects displayed similar cycling in infancy but eventually locked into a stable pattern of upwardly trending antibody production and TH2-polarized cellular immunity. The latter was associated with stable expression of IL-4 receptor in allergen-specific TH2 memory responses, which was absent from responses during infancy. Risk for persistent wheeze was strongly linked to early sensitization and in turn to early infection. Integration of these data by means of logistic regression revealed that attaining mite-specific IgE titers of greater than 0.20 kU/L by age 2 years was associated with a 12.7% risk of persistent wheeze, increasing progressively to an 87.2% risk with increasing numbers of severe lower respiratory tract illnesses experienced. Conclusion: The risk for development of persistent wheeze in children can be quantified by means of integration of measures related to early sensitization and early infections. Follow-up studies along similar lines in larger unselected populations to refine this approach are warranted. © 2010 American Academy of Allergy, Asthma & Immunology.